2020
DOI: 10.33788/rcis.68.19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Attraction of Social Networking Sites of Taiwan Toys on Consumers’ Purchase Intention

Abstract: The change in the original business model of social networking sites connects people in the world together and transfer social activity in real life onto networks that people could precede social activity without going out. It is the social model mostly expected by modern people. Nonetheless, such a behavior model slowly changes the marketing pattern of electronic commerce. The high standardization of model toys facilitates the use and assembly. Unlike clothing which needs to try on or food which could easily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
(20 reference statements)
0
0
0
Order By: Relevance
“…Abdul Hafeez, Manzoor, and Salman [7] studied the restaurant industry in Karachi and concluded that social networking sites play an important role in shaping consumers' purchase intentions. Chen and Lin [4] adopted the method of random sampling in their research and distributed 420 questionnaires to members of social networking sites in the toy industry in Taiwan. A total of 327 efficient responses were retrieved, with a retrieval rate of 78%.…”
Section: Industry Influencementioning
confidence: 99%
See 2 more Smart Citations
“…Abdul Hafeez, Manzoor, and Salman [7] studied the restaurant industry in Karachi and concluded that social networking sites play an important role in shaping consumers' purchase intentions. Chen and Lin [4] adopted the method of random sampling in their research and distributed 420 questionnaires to members of social networking sites in the toy industry in Taiwan. A total of 327 efficient responses were retrieved, with a retrieval rate of 78%.…”
Section: Industry Influencementioning
confidence: 99%
“…The aim of this study is to investigate how social networking site attractiveness affects Taiwanese toy customers' desire to purchase by utilizing social networking site attributes. Chen and Lin's [4] research on the toy industry in Taiwan shows that the attractiveness of social networking sites will affect consumers' purchase intention. These industry-specific studies highlight the versatility of social media as a tool to influence buying behavior across different industries.…”
Section: Industry Influencementioning
confidence: 99%
See 1 more Smart Citation